Phase interactions in Ni-Cu-Al2O3 mixed oxide oxygen carriers for chemical looping applications - Huang, Jijiang (2021)
Chemical looping processes present great potentials to achieve carbon capture and fuel conversion with high thermodynamic efficiencies. Well-known applications of chemical looping include combustion and methane reforming, where phase interactions in oxygen carriers play important roles in determining the process performance. In this study, we systematically investigate the interactions between various phases in Ni-Cu-Al2O3 mixed oxides oxygen carriers, which were prepared from layered double hydroxides precursors, synthesized hydrothermally using urea and metal nitrates. It appears that the addition of 32–45 wt% Al2O3 was sufficient to prevent sintering effects over 100 redox cycles at 800 °C, 1 atm, using methane as the fuel. The oxide phases and their compositions were determined using a set of complementary analytical techniques, allowing us to establish relationships between (i) the compositions of the mixed oxides, (ii) the chemical activity of the various types of lattice oxygen present and (iii) the distributions of gaseous products of chemical looping methane oxidation. We found that the mutual doping between NiO and CuO leads to enhanced lattice oxygen activities, whilst the solid solution of NiAl2O4 and CuAl2O4 leads to reduced lattice oxygen activity in the spinel phase, which also turns out to be particularly resistant to carbon deposition. The generality of the composition – activity - performance relationship is demonstrated by the successful prediction of the product distributions of methane oxidation based on solely the elemental compositions of the oxygen carriers. These findings enable the rational formulation of Ni-Cu-Al2O3 oxygen carriers for methane conversion with precise control of product selectivity.